Relating the Biogeochemistries of Zinc, Cobalt, and Phosphorus to Phytoplankton Activities in the Sea - Wisniewski, Rachel J. (2006)
This thesis explores the potential of zinc, cobalt and phosphorus to influence phytoplankton production. In the North Pacific and Bering Sea, total zinc concentrations were measured in the near-surface and in deep profiles. Zinc speciation was measured with a novel anodic stripping voltammetry method. Zinc's ability to influence primary production in the North- Pacific was demonstrated in a shipboard incubation and by comparing two phytoplankton pigments to zinc concentrations. In the North Atlantic, total dissolved zinc and cobalt were measured along with dissolved inorganic and organic phosphorus. In parts of the North Atlantic, zinc and cobalt were decoupled. The relationship between cobalt and inorganic phosphorus suggests that cobalt drawdown may be related to an alkaline phosphatase related demand. This compliments a shipboard incubation where alkaline phosphatase activity increased after cobalt addition. The presence of alkaline phosphatase activity indicated that the phytoplankton community in the Sargasso Sea was experiencing phosphorus- stress. Shipboard incubations generally confirmed this with chlorophyll- increases observed after additions of phosphate and dissolved organic phosphorus. This suggests that dissolved organic phosphorus may be an important phosphorus source in low phosphorus environments. This thesis contributes to the understanding of how phosphorus, zinc, and cobalt influence primary production. The original document contains color images.